Menghidupkan Pemikiran Gusdur dalam Pendidikan Nasional - Ach. Syaiful; Ahmad Hanif Fahruddin (LPTNU Sumenep, 2024)
National education must be strengthened with the spirit of Gusdur's thoughts on peace, local wisdom and pluralism. As Gusdur's three thoughts that must live in the national education process. This study uses a literature review with three journals as primary sources. The results of this study are that there are three Gusdur's thoughts that must be alive today, especially in national education, Gusdur's thoughts about peace in the aspect of national education. That the cultural components of the archipelago can become a core part of national education. Both said that Gus Dur took a socio-cultural approach that national education must be built with an insight into Indonesian culture. Second, the idea of ​​indigenization of Islam is a breakthrough in the thinking of Islamic figures who provide solutions in dealing with the social problems of Islamic society in Indonesia. Local wisdom is precisely Gusdur's thought which has the dimension of educational modernism. Third, Gusdur's thinking about pluralism, pluralist thinking must be included in school learning, strengthening it in the form of attitudes and real work through extra activities at school. There are moral knowing, moral feeling and also moral action, these three stages in building character are also relevant to Gusdur's views on the three dimensions of pluralism that can be applied in national education.